The Effect Of Training On Employee Performance At The South Binjai Sub-District Sub-District Office - Ida Sufianty; Muhammad Isa Indrawan (International Journal of Management, Economic and Accounting, 2024)
This type of research is a causal associative quantitative research with the aim of analyzing the pattern of relationships between variables and finding out the influence between two independent (exogenous) variables on bound variables. This research was carried out at the South Binjai Sub-district Office, with a population of 117 employees. The sampling technique used is saturated sampling, which is a sample selection technique in which all members of the population are sampled. The data used came from the results of a questionnaire distributed to respondents consisting of all employees. The results of the study show that Training has a positive and significant effect on Employee Performance. This is evidenced by the t-count value of 15.130 > t-table of 1.98081, as well as a significance value of 0.000 < 0.05. The regression coefficient of 1.422 indicates that every 1 point increase in Training will lead to an increase in Employee Performance by 1.422 points, assuming other variables remain constant. In addition, the results of the determination coefficient test showed an Adjusted R Square value of 0.666 or 66.60%, which showed that Training had a very high influence on Employee Performance, with the remaining 33.40% influenced by other factors that had not been studied in this study. Overall, the results of this study identify that the improvement of Training can contribute to the improvement of Employee Performance at the South Binjai Sub-district Office.